2019
DOI: 10.1186/s12974-019-1474-8
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin ameliorates neuroinflammation-induced depressive-like behavior through inhibition of toll-like receptor 4 expression via the PI3K/AKT/FoxO1 pathway

Abstract: Background Baicalin, which is isolated from Radix Scutellariae , possesses strong biological activities including an anti-inflammation property. Recent studies have shown that the anti-inflammatory effect of baicalin is linked to toll-like receptor 4 (TLR4), which participates in pathological changes of central nervous system diseases such as depression. In this study, we explored whether baicalin could produce antidepressant effects via regulation of TLR4 signaling in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
162
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(175 citation statements)
references
References 73 publications
5
162
1
Order By: Relevance
“…Activated microglia are the major source of proinflammatory cytokines, such as TNF-a, IL-1b, and IL-6, in the CNS (Yang M. et al, 2018). Preclinical and clinical studies have proposed that proinflammatory cytokines are associated with the pathogenesis of depression (Karson et al, 2013) and that an increase in pro-inflammatory cytokines contributes to depressive-like behaviors (Raison et al, 2006;Guo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated microglia are the major source of proinflammatory cytokines, such as TNF-a, IL-1b, and IL-6, in the CNS (Yang M. et al, 2018). Preclinical and clinical studies have proposed that proinflammatory cytokines are associated with the pathogenesis of depression (Karson et al, 2013) and that an increase in pro-inflammatory cytokines contributes to depressive-like behaviors (Raison et al, 2006;Guo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing amounts of preclinical and clinical research have shown that proinflammatory cytokines might contribute to depression. The proinflammatory cytokines tumor necrosis factor-a (TNF-a) and interleukin-6 (IL-6) play critical roles in the process of inflammation and can induce depressive disorders (Wright et al, 2005;Guo et al, 2019). The levels of IL-6 and TNF-a were reported to be increased in the blood and cerebrospinal fluid of MDD patients (Syed et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Upstream effectors of PI3K signaling are dysregulated in the LHb in a rat model of depression 46 . Phosphorylation of PI3K is implicated in the antidepressant effects of baicalin in a mouse model of depression 47 . We predict that downregulation of PI3K in the RMTg-projecting neurons after stress would be a compensatory adaptation that reduces their excitability, thereby disinhibiting the monoaminergic neurons in the DRN and VTA.…”
Section: Discussionmentioning
confidence: 99%
“…LPS is widely used to induce neuroin ammation [2,3,49,54,62]. Numerous studies showed that LPS treatment could induce central in ammatory response associated with proin ammatory cytokines production, glial cell activation, as well as ROS and RNS generation [2,5,7,40,44,47,54,[63][64][65][66][67][68][69]. Furthermore, activated NF-κB also promotes neurotoxic cytokines and ROS production of glial cells [2,3,5].…”
Section: Discussionmentioning
confidence: 99%
“…Major depressive disorder (MDD) is a multifactorial severe psychiatric illness characterized by the lake of interest, a signi cant change in mood which is accompanied by a disturbance in sleeping, eating, and anhedonia [1][2][3][4][5]. It is estimated that MDD will be the second leading illness affecting 10% of the population world widely up to 2020 [6].…”
Section: Introductionmentioning
confidence: 99%